Hepatoprotective Effect of Corn Silk Infusion in Male Wistar Rats - Arba Pramundita Ramadani; Hady Anshory Tamhid; Tika Luthfi Sadrina; Jasno Jasno; Mabrurotul Mustafidah (EKSAKTA: Journal of Sciences and Data Analysis, 2020)
The use of medicinal plants in treating various disease has been reported since long time ago, including for hepatic disease. Corn silk contains phytochemicals of medical benefit such as flavonoids compounds which act as antioxidant agents and has been widely reported possess hepatoprotective effect. Using a model of carbon tetrachloride (CCl4)-induced hepatotoxicity in 36 male Wistar rats, this study investigated the effect of corn silk infusion and assessed using enzymes produced by the liver in plasma [alkaline phosphatase (ALP) and liver glutathione (GSH)]. The corn silk infusion (in 50, 100, and 200 mg/kg BW doses) were administered 24 hours after CCl4-induction liver damage with 3ml/kg BW CCl4 in olive oil (1:1, v/v), intraperitoneally for seven days. Along with corn silk groups, distilled water (0.2 mL/kg BW) and Curcumin (100 mg/kg BW) were given for induction and drug control, respectively. In the end of the study (8th day), the level of both ALP dan GSH were measured. The differences among groups for GSH and ALP level were statistically calculated using ANOVA method.  The result showed that the corn silk infusion is active at 200 mg/kg BW based on both ALP (18.74% decreased) and GSH (5-7% increased) level. Moreover, the flavonoid compound was detected on the infusion that may contribute on its hepatoprotective activity. In conclusion, corn silk infusion owned hepatoprotective effect in male Wistar rats.